p40phox-Deficient Mice Exhibit Impaired Bacterial Clearance and Enhanced Pro-inflammatory Responses during Salmonella enterica serovar Typhimurium Infection - Li, Yali; Lv, Meili; Su, Chienwen; Long, Shaorong; Zhang, Wei; Conway, Kara L.; Li, Weifen; Xavier, Ramnik J.; Shi, Hai Ning (Frontiers in Immunology, 2017)
Salmonella enterica serovar Typhimurium (S. Typhimurium) is a major cause of acute gastroenteritis in humans. During infection, reactive oxygen species (ROS), generated from NADPH oxidase (a multisubunit enzyme complex), are required for pathogen killing upon phagocytosis and for regulating pro-inflammatory signaling in phagocytic cells. Mutations in subunits forming the NADPH complex may lead to enhanced susceptibility to infection and inflammatory disease. Compared to other NADPH oxidase subunits, the function of p40phox is relatively understudied, particularly in the context of intestinal bacterial infection. In this study, we utilized genetically engineered mice to determine the role of p40phox in the response to S. Typhimurium infection. We show that mice lacking p40phox are more susceptible to oral infection with S. Typhimurium, as demonstrated by significantly enhanced bacterial dissemination to spleen and liver, and development of exacerbated bacterial colitis. Moreover, we demonstrate that the increased infection and disease severity are correlated with markedly increased F4/80+ macrophage and Ly-6G+ neutrophil infiltration in the infected tissues, coincident with significantly elevated pro-inflammatory cytokines (IL-1β and TNF-α) and chemoattractant molecules in the infected tissues. Functional analysis of macrophages and neutrophils further shows that p40phox deficiency impairs bacteria- or PMA-induced intracellular ROS production as well as intracellular killing of Salmonella. These observations indicate that the p40phox subunit of NADPH oxidase plays an essential role in suppressing intracellular multiplication of Salmonella in macrophages and in the regulation of both systemic and mucosal inflammatory responses to bacterial infection.